EFEKTIVITAS MEDIASI DALAM PENYELESAIAN KREDIT BERMASALAH (STUDI KASUS DI KOPERASI JAYA MANDIRI TABANAN) - Asriani, Ni Ketut Yanik Asriani; Ida Ayu Windhari Kusuma Pratiwi; I Kadek Adi Surya; Ida Bagus Wirya Dharma (Universitas Tabanan, 2025)
Koperasi is an organization established to improve collective welfare, one of which is through savings and loan facilities that help members meet living and business needs. Problems arise when members fail to fulfill their credit repayment obligations. An effective solution is alternative dispute resolution through mediation, a peaceful process assisted by a neutral third party without involving the court. This study applies a socio-legal method, examining law in relation to social reality based on objective data, information, and opinions collected in the field. Theoretical foundations include Dispute Resolution Theory, Mediation Theory, and Non-Performing Loan Theory. Findings show that mediation in Koperasi Jaya Mandiri Tabanan is effective in resolving problematic loans. The process emphasizes a family approach, open communication, and consensus, resulting in agreements without litigation. However, challenges occur when debtors fail to attend mediation despite being summoned, which hinders deliberation and reflects a lack of responsibility. Therefore, more intensive communication is needed to encourage debtor participation and ensure the effectiveness of mediation.